The U.S. Labor Movement in the 20th and Early 21st Century A Critical Analysis - Barrington, Adam. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book provides a critical analysis of the labor movement in the United States in the 20th and early 21st century. It explores ideological trends within the labor movement and its conflicts with capital and the state. It identifies class-collaborationism between the conservative labor bureaucracy and the capitalist class as the primary source of U.S. labor's precariousness and fragility. It argues that the U.S. labor movement at its most radical and militant stage was an effective force for change against the power structure in the early 20th century. At the opposite end, it also argues that today's institutionalized labor movement led by the AFL-CIO hinders labor's historic struggle against capital and aids in the maintenance of the existing capitalist order. The book concludes by assessing the prospects for the future development of militant working-class activism and identifies essential components of an emerging radical labor movement that is capable of effectively challenging the capitalist system in the period ahead. Adam Barrington is a labor activist and community organizer who lives in Cleveland, Ohio, USA. He is a member of the Industrial Workers of the World (IWW) and a delegate for Service Employees International Union (SEIU) 1199. He served as a labor organizer for Local 4041 of the American Federation of State, County, and Municipal Employees (AFSCME) in Reno, Nevada, USA. He received his Master's degree in Sociology at the University of Nevada, Reno, where he conducted research on the history of the U.S. labor movement. He plans to pursue future doctoral studies in sociology focused on the contemporary labor movement in the United States.
1 Introduction -- References -- 2 What Happened to the U.S. Labor Movement? -- After WWII -- Labor and Politics -- Exclusive Representation and Systemic Restraints -- Solidarity and Direct Action -- Violence Against Labor -- The Cold War and Institutionalization -- References -- 3 The Early U.S. Labor Movement -- Beginning -- A House Divided -- World War and Class War -- The Rise of the CIO: Organizing the Unorganized -- One Industrial Union Grand -- No More Reds in the Union -- Red Unionism: An Autopsy -- U.S. Labor and Anticommunism -- The Graveyard of Social Movements -- References -- 4 The U.S. Labor Movement Since 1955 -- Labor and the Democrats: A Parasitic Relationship -- The AFL-CIO and the CIA -- Worker Militancy After 1955 -- Reckoning with the Past and Organizing in the Present -- References -- 5 Filling the Void: The Reactionary Response to Neoliberalism and Its Crises -- Pseudo-Populism: Exploiting Discontent -- Ethno-Nationalism: Identity Politics of the Right -- Authoritarianism/Fascism -- The Need for a New Labor Movement -- References -- 6 Rebuilding the Labor Movement and Prospects for the Future -- Putting Workers Back at the Helm -- What Will a New Labor Movement Look Like? -- New Labor, New Politics -- References -- 7 Conclusion: A World to Win -- Bibliography.
Keywords: Industrial sociology; Marxian school of sociology; Labor; History; Political sociology; Social structure; Equality; Economic sociology; Sociology of Work; Marxist Sociology; Labor History; Political Sociology; Social Structure; Economic Sociology